Implementation of Smart Discrimination Training to Improve Discrimination Skills in Autism Spectrum Disorder - Rudy Sutadi; Kuncono Teguh Yunanto; Alam Zeb Khattak; Catur Prasetyo; Arneliza (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2026)
Autism is a severe neurobiological developmental disorder appearing before age three, with deficits in communication and social interaction that often persist without intervention. Discrimination Training (DT), vital for children with ASD, involves distinguishing instructions, concepts, and objects. Conventional DT presents multiple stimuli simultaneously, which can confuse children and cause unstable responses. This study introduces Smart Discrimination Training (Smart DT) and tests its effectiveness in two types of children with ASD using a developmental, single-subject experimental design. Data show that both types of children with ASD, who previously had difficulty with discrimination, improved and maintained their skills. Smart DT proves effective as a structured training method for more complex discrimination tasks in children with ASD.